1990
DOI: 10.1007/bf02718198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a bacterial extract on antigen presentation and protection against experimental infections

Abstract: Although substances known as immunodulators are usually used to stimulate nonspecific immunity, their mode of action is not well understood. In an effort to clarify this mechanism, we investigated the effect of a lyophilized bacterial extract (Broncho-Vaxom) on experimental infections, on normal or irradiated mice, and on antigen processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Broncho-Vaxom (BV), a bacterial lysate of 21 strains of 8 bacteria (Staphylococcus aureus, Haemophilus influenzae, Streptococcus pyogenes, Moraxella catarrhalis, Klebsiella pneumoniae, Klebsiella ozaenae, Streptococcus viridans and Diplococcus pneumoniae), has been shown to boost the immunological response 21 . Bacterial lysates have pleiotropic immunomodulating effects on both the innate and adaptive immune responses 22 , 23 . Research has shown that such lysates are able to induce an immunoregulatory response within mucosa-associated lymphoid tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Broncho-Vaxom (BV), a bacterial lysate of 21 strains of 8 bacteria (Staphylococcus aureus, Haemophilus influenzae, Streptococcus pyogenes, Moraxella catarrhalis, Klebsiella pneumoniae, Klebsiella ozaenae, Streptococcus viridans and Diplococcus pneumoniae), has been shown to boost the immunological response 21 . Bacterial lysates have pleiotropic immunomodulating effects on both the innate and adaptive immune responses 22 , 23 . Research has shown that such lysates are able to induce an immunoregulatory response within mucosa-associated lymphoid tissue.…”
Section: Introductionmentioning
confidence: 99%
“…OM-85 (Broncho-Vaxom Ò , Broncho-Munal Ò , Vaxoral Ò , Ommunal Ò , Paxoral Ò ) is an immunomodulator comprising lyophilized bacterial lysates from the eight major strains responsible for RTIs (Haemophilus influenzae, Streptococcus pneumoniae, Klebsiella pneumoniae, Klebsiella ozaenae, Staphylococcus aureus, Streptococcus pyogenes, Streptococcus viridans, and Moraxella catarrhalis). OM-85 has pleiotropic immunomodulating effects on both the innate and adaptive immune responses [15][16][17]. There is an extensive body of evidence showing the safety and efficacy of OM-85 in the prevention of RTIs in children and adults regardless of the etiology, including in those with impaired immunity [15,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It was interesting to notice that during the latter study an IgE decrease and a T4/T8 increase in bronchoalveolar lavage, were detected.Numerous scientific studies, both in vitro and in vivo, have been carried out to determine the mechanisms by which OM-85 BV stimulates immune system. Manuel et al established that OM-85 BV activates mouse peritoneal and bone marrow macrophages in vitro[12]. Further work performed by Fontages et al, showed that OM-85 BV stimulated the release of prostaglandin E2, IL1 and TNF-a from alveolar macrophages[13].…”
mentioning
confidence: 99%